2019
DOI: 10.3390/ijms20040856
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Percutaneous Trephination with a Platelet Rich Plasma Intrameniscal Injection for the Repair of Degenerative Meniscal Lesions. A Prospective, Randomized, Double-Blind, Parallel-Group, Placebo-Controlled Study

Abstract: Meniscal tears are the most common orthopaedic injuries, with chronic lesions comprising up to 56% of cases. In these situations, no benefit with surgical treatment is observed. Thus, the purpose of this study was to investigate the effectiveness and safety of percutaneous intrameniscal platelet rich plasma (PRP) application to complement repair of a chronic meniscal lesion. This single centre, prospective, randomized, double-blind, placebo-controlled study included 72 patients. All subjects underwent meniscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(106 citation statements)
references
References 50 publications
3
102
1
Order By: Relevance
“…As a result of this limitation, it is not known whether the treatment effect was caused by injection into the meniscus or into the intra-articular space, or a combination of both. As well, percutaneous trephination of the meniscus with normal saline and PRP has shown some treatment effect for horizontal tears [34] and thus may have contributed to the treatment effect observed in the present study. To mediate this limitation in a future study, a control group of individuals who solely receive intra-articular injections without injection into the meniscus and another which receives trephination of the meniscus with normal saline could be included.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As a result of this limitation, it is not known whether the treatment effect was caused by injection into the meniscus or into the intra-articular space, or a combination of both. As well, percutaneous trephination of the meniscus with normal saline and PRP has shown some treatment effect for horizontal tears [34] and thus may have contributed to the treatment effect observed in the present study. To mediate this limitation in a future study, a control group of individuals who solely receive intra-articular injections without injection into the meniscus and another which receives trephination of the meniscus with normal saline could be included.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, a double-blind RCT was conducted to compare outcomes of meniscus trephination with or without PRP injection; failure (defined as meniscus non-union observed in the magnetic resonance arthrography or arthroscopy) was noted for 70% of patients in the control group, while only 48% failure was noted in the PRP group. There was also greater symptom improvement and less eventual APM in the PRP group [34]. The minimal benefits generally observed in the use of PRP to treat osteoarthritis and meniscus tears discouraged its use in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Two RCTs [47,48] and five non-randomized studies [49][50][51][52][53] evaluated the use of PRP in meniscus healing. In five studies, PRP was injected after arthroscopic meniscus repair [47,49,50,52,53], in one study patients underwent open meniscal repair with an adjunct of PRP [51], and in another the authors compared percutaneous meniscal trephination with or without PRP [6].…”
Section: Meniscal Repairmentioning
confidence: 99%
“…One study did not provide any objective radiographic outcomes, only commenting "some" MRIs [49]. The pooled estimates for all six studies showed significant differences in favor of PRP (p = 0.0003), but due to the diversity of clinical trial types, synthesis provided only level of evidence III type data (retrospective cohort Six studies reported failure rates of meniscus healing, two randomized studies using MRI and second-look arthroscopy showed significant differences in favor of PRP (p = 0.006) [47,48], and another four non-randomized studies also showed significant differences in favor of PRP (p = 0.02) [50][51][52][53]. In three studies the failure rate was defined by the need for revision surgery [50,52,53] and in the final study, MRI was used to assess meniscus healing [51].…”
Section: Meniscal Repairmentioning
confidence: 99%
“…In this meta-analysis, the change in the VAS score was significantly smaller in the experimental group than in the control group; in other words, the pain intensity was lower in the experimental group than in the control group. In the sensitivity analysis, two articles by Kaminski et al 14,16 were omitted; as a result, the I 2 decreased to 34% and the conclusion remained unchanged. The heterogeneity might have been the result of a longer follow-up time in the studies conducted by Kaminski et al 14,16 ; i.e., the pain intensity was low at the last follow-up, resulting in high heterogeneity.…”
Section: Discussionmentioning
confidence: 99%